THE ROLE OF REMUNERATION, MOTIVATION, AND JOB SATISFACTION IN ENHANCING EMPLOYEE PERFORMANCE: A STUDY OF WALED CIREBON HOSPITAL - Nurul Ainy; Bambang Sumardi (Journal Of Resource Management, Economics And Business, 2023)
Purpose: This study aims to determine the effect of Remuneration, Motivation and Job Satisfaction on Employee Performance at Rsud Waled Cirebon.Research Methodology: This research uses a survey method. The survey method is used to solve actual large-scale issue problems with very large populations, so a large sample size is required.Results: There is a partial remuneration effect on the performance of employees of the Cirebon Waled Hospital. There is a partial influence of motivation on the performance of employees of the Cirebon Waled General Hospital. There is a partial effect of job satisfaction on the performance of employees of the Cirebon Waled General Hospital. There is a simultaneous influence of Remuneration, Motivation and Job Satisfaction on Employee Performance at Rsud Waled Cirebon.Limitations: this research is not without limitations, namely the object of research only focuses on the performance of employees at the Cirebon Hospital Waled.Contribution: This research will contribute to the field of human resources in the development of work productivity as well as communication, work attitudes and competencies